AUTHENTIC MATERIALS SELECTION IN HOSPITALITY PROGRAM AT STATE VOCATIONAL HIGH SCHOOL (SMKN) 1 BUDURAN SIDOARJO - Abdul Kholik (JAMBI-ENGLISH LANGUAGE TEACHING, 2016)
Authentic Materials are helpful for the students of vocational high school to know the real use of English in the real context. Using authentic materials is expected to meet an ideal teaching materials to build students’ interest in learning English since there is no coursebook that can be ideal for any particular class (Brian, 2001) and teaching materials for vocational high school tend to be viewed as distinct and separate from general coursebook (Alan, 1995). However, authentic materials should be selected carefully to get the proper authentic materials that could make students interested, motivated, and possibly bring authentic learning. Thus, there are two research questions that need to be answered; those are what kinds of authentic materials used by the teacher and the criteria used by the teacher to select them to be used in English teaching in Hospitality program at SMKN 1 Buduran Sidoarjo. The research used descriptive qualitative design with narrative approach since the focus of the research was to explore more on teacher’s experience in using authentic materials to be used in English teaching of hospitality program. The data was collected through documentation and interview technique using document analysis checklist and interview guideline as the instruments of the research. The result of the study showed that the teacher used both of two categories of authentic materials; those are authentic print materials such as bills, order forms, signs, pictures, etc. and authentic auditory materials such as videos, songs, etc. Selecting those authentic materials, the teacher considered four criteria: 1) authentic materials should appropriate to basic competence and students need, 2) authentic materials should be interesting, 3) authentic materials should be understandable, and 4) authentic materials should up-to-date or do not seem obsolete to be used.